Comparison of DC-DC power converters used in thermoelectric power generation - Hong, Wei Xiang (2017)
Due to poor efficiency in current system and higher awareness emphasize on environmental concerns, waste heat recovery technologies aims to bridge the gap of increasing efficiency. In order to achieve better efficiency, a DC-DC power converter is designed to meet the Maximum Power Point (MPP) of the Thermoelectric Generator (TEG) when varying the duty cycle. Two separate converters will be design to cater frequencies of 10kHz and 100kHz.